RANCANG BANGUN PENGUPAS KULIT KACANG MENGGUNAKAN MIKROKONTROLER ATMEGA 8 DAN PANEL SURYA 20 WP - Andi, Hendra Jaffri; Yanie, Ahmad; Siregar, Lisa Adriana (Lembaga Riset dan Pengembangan Sumatera Utara, 2023)
To support the production process of a home industry or large industry, tools or machines are needed. For example, in an industry that produces peanut bread, there is a process of peeling the peanuts, both the shells and the shells, which takes a lot of time and labor. To help overcome these problems, this research designed a semi-automatic peanut shell peeler. The machine works as a grinder where the roasted nuts are put into a grinding mill that has been spaced so that the peanuts that enter will be peeled. The machine is driven by an electric current that is to run a permanent magnet DC motor and sensor. For that we need a source of DC electricity. As a supplier of electricity, NRE energy is utilized, namely sunlight obtained by a 20WP solar panel and equipped with a backup battery to store electric current. It is hoped that the designed machine can support productivity and can be used in villages or remote areas where there is no PLN electricity.